El efecto de la autocorrecion en la illusion de Müller-Lyer - S. de Vicente, Maria Luisa (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
With a sample of 28 individuals an experiment can be made of self-correction of illusion of Müller-Lyer.